USE OF CONCILIATION AS A METHOD FOR INTERNATIONAL INVESTMENT DISPUTE SETTLEMENT IN INTERNATIONAL INVESTMENT AGREEMENT - Basalamah, Ienas (Transnational Business Law Journal, 2023)
An International Investment Agreement is an agreement formed between countries which provides a legal umbrella for carrying out foreign investment activities for related parties. One of the problems criticized in international investment agreements is related to settlement methods that tend to use arbitration, which is currently widely criticized in practice. The aim of this research is to assess the effectiveness of conciliation as a method of resolving international investment disputes and the advantages of using conciliation as a method of resolving international investment settlements for Indonesia. This research uses descriptive analytical methods and data analysis is carried out using qualitative juridical methods. From the results of this research, it can be seen that in practice conciliation is still not widely used to complete a settlement. However, seeing the many criticisms of settlements through arbitration, it can be said that there is a push to use other settlement alternatives to complete a settlement. In this case, conciliation can be an option and has many advantages considering the characteristics of fast, efficient and flexible conciliation.